DOI: 10.25148/etd.fi14060806
|View full text |Cite
|
Sign up to set email alerts
|

What secondary english to speakers of other languages (ESOL) teachers know about social and academic language and instructional strategies for limited english proficient students

Abstract: Chin, Judy, "What secondary english to speakers of other languages (ESOL) teachers know about social and academic language and instructional strategies for limited english proficient students" (2002 The dissertation of Judy Chin is approved.Dean Linda Blanton Tashakkori's observations and highly focused questions from the inception of the study to its completion were greatly appreciated. Dr. Sandra Fradd, whose broad knowledge and vast experience in the field of second language acquisition, provided critical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Also hypothesized in this study was that listeners would rate the L2 learners’ productions in the word‐final position as having less accuracy than those produced in the word‐initial position. This hypothesis was based on the relative lack of final consonant endings in both Mandarin and Korean (Cheng, 1991; Fang & Ping‐an, 1992; Nasukawa, 2004). This study generally found that the L2 learners’ obstruent productions were rated to have greater accuracy when produced in the word‐initial position compared to the word‐final position.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also hypothesized in this study was that listeners would rate the L2 learners’ productions in the word‐final position as having less accuracy than those produced in the word‐initial position. This hypothesis was based on the relative lack of final consonant endings in both Mandarin and Korean (Cheng, 1991; Fang & Ping‐an, 1992; Nasukawa, 2004). This study generally found that the L2 learners’ obstruent productions were rated to have greater accuracy when produced in the word‐initial position compared to the word‐final position.…”
Section: Discussionmentioning
confidence: 99%
“…Second language learners of English frequently substitute the fricative /s/ for /θ/ and the fricative /f/ for /θ/ and for /v/ (Cheng, 1991;Slobin, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations